Kajian Etnofarmasi Penggunaan Tumbuhan Obat Sebagai Alternatif Pengobatan Diare Oleh Masyarakat Suku Osing Dusun Krajan - Amira Septa Sanjaya; Hartono Hartono; Truly Dian Anggraini (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2023)
Diarrhea is a disease whose existence is still a global health problem, including Indonesia. Diarrhea is in the top 10 diseases that still occur frequently and is ranked 5th in the Osing Tribe. For the treatment of diarrhea, the Osing tribe still uses plants as medicinal plants that are used for generations. This study was conducted to examine how ethnopharmacy in the Osing tribe is intended as a preliminary study for the development of traditional medicine carried out by the Osing tribe as traditional medicine/phytopharmaca. This research is a descriptive study using qualitative methods with sampling techniques using snowball sampling through open-ended interviews by filling out informant information sheets and involving 22 informants from the Osing Tribe, Krajan hamlet, Kemiren, Glagah, Banyuwangi, East Java. The results of the ethnopharmaceutical research in the Osing Tribe showed that there were 8 types of plants and an analysis was carried out using ICF (Informant Consensus Factor) with the results of 0.6 being interpreted as being trusted and used as a hereditary treatment, PPV (Plant Part Value) to calculate the plant part used. with a yield of 50% leaves, 23% fruit, 27% rhizome and FL (Fidelity Level) to determine the types of plants most often used in treating diarrhea with the highest yield of 100%, including Psidium guajava L and Manihot esculenta.